Descriptive characterization of the cerebrospinal meningitis outbreak in Zamfara State, 2017-18 - Ahmad Njidda; Ismail Raji; Sulaiman Lawal; Hakeem Yusuf; Evaristus Aniaku; Rabi Usman; Auwal Usman Abubakar; Jamilu Nikau; Moreen Kamateeka; Muhammad Shakir Balogun; Patrick Nguku (Journal of Interventional Epidemiology and Public Health)
Introduction: Cerebro-spinal meningitis (CSM) is an epidemic-prone disease characterized by inflammation of the meninges. From epidemiological week 36, 2017 through epidemiological week 21, 2018, Zamfara State reported an outbreak of CSM that affected all the 14 Local Government Areas (LGAs). Therefore, we conducted a descriptive analysis of the outbreak to determine its epidemiology.